ING2 Controls Mitochondrial Respiration via Modulating MRPL12 Ubiquitination in Renal Tubular Epithelial Cells - Yang, Ying; Li, Chensheng; Gu, Xia; Zhen, Junhui; Zhu, Suwei; Lv, Tingting; Wan, Qiang; Liu, Yi (Frontiers in Cell and Developmental Biology, 2021)
Mitochondrial injury of tubular epithelial cells (TECs) is the key pathogenic event underlying various kidney diseases and a potential intervening target as well. Our previous study demonstrated that ING2 is ubiquitously expressed at tubulointerstitial area within kidneys, while its role in regulating TECs mitochondrial respiration is not fully elucidated. To clarify the roles of ING2 in mitochondrial homeostasis of TECs and pathogenesis of acute ischemic kidney injury, western blot, PCR, immunofluorescence, immunoprecipitation, and oxygen consumption rate assay were applied to address the roles of ING2 in modulating mitochondrial respiration. We further complemented these studies with acute ischemic kidney injury both in vitro and in vivo. In vitro study demonstrated ING2 could positively control TECs mitochondrial respiration. Concurrently, both mRNA and protein levels of mtDNA encoded respiratory chain components were altered by ING2, suggesting ING2 could regulate mtDNA transcription. In mechanism, ING2 could regulate the ubiquitination of a newly identified mitochondrial transcription factor MRPL12, thereby modulating its cellular stability and abundance. We also demonstrated ING2-mediated modulation on mtDNA transcription and mitochondrial respiration are involved in serum-deprivation induced TECs injuries. Finally, Immunohistochemistry study revealed that ING2 expression was significantly altered in kidney biopsies with acute ischemic kidney injury. In vivo study suggested that kidney specific ING2 overexpression could effectively ameliorate acute ischemic kidney injury. Our study demonstrated that ING2 is a crucial modulator of TECs mitochondrial respiration. These findings suggested a unrecognized role of ING2 in TECs mitochondrial energetic homeostasis and a potential intervening target for TECs mitochondrial injury associated pathologies.